ENGLISH NOUN PHRASES OF NARRATIVE TEXT AND NEWS ARTICLE: A CONTRASTIVE ANALYSIS - Ardik Ardianto (UIN Raden Mas Said Surakarta, 2023)
Noun phrases, in either language in general or English in particular, are one of the pivotal topics in formal linguistics. This paper aimed to contrast the similarities and differences of the patterns of ideational structure and syntactic functions of noun phrases in two different text genres. It employed systemic functional linguistic approach using both Ideational structure analysis and syntactical analysis of noun phrases in narrative texts and news articles. The findings of this study show that noun phrases in narrative texts tend to be shorter and simpler, especially as they occupy the subject and object functions. The forms of pre-modifiers used also tend to be simpler (ranging from the use of one or two pre-modifiers only). The same case occurs in post-modifier forms as well. In contrast, news articles tend to use complex phrase structures (two or even three pre-modifiers at once) which are coupled with other complex information in the post-modifiers. Appositives appear several times as post-modifiers to complete the information in the noun phrases. In conclusion, these differences prove that the determinism of writing style in each genre has a significant share in determining the pattern complexity of the noun phrase structures therein.